SUCCESSFUL LONG-TERM REMISSION IN AGGRESSIVE YOUNG-ONSET CHRONIC LYMPHOCYTIC LEUKEMIA WITH IBRUTINIB AND VENETOCLAX: A DECADE-LONG CASE STUDY - Naciye Nur Tozluklu; Birol Guvenc (Hematology, Transfusion and Cell Therapy)
Chronic Lymphocytic Leukemia (CLL) typically affects older individuals and is frequently associated with genetic mutations that help predict its progression. However, this report presents a rare case of aggressive CLL in a young woman with no unfavorable genetic markers, who achieved lasting remission following the use of dual targeted therapy, after standard treatments repeatedly failed.A 40-year-old woman was diagnosed with CLL during a routine blood examination. Despite lacking any high-risk genetic indicators, her disease advanced swiftly over the next ten years. Initial treatment with CVP (cyclophosphamide, vincristine, prednisone) provided only a brief partial remission. A subsequent course of R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) also led to relapse within a few months.Ibrutinib was introduced as a single-agent treatment but failed to control the disease. The patient's condition continued to deteriorate, with recurring lymph node enlargement and rising lymphocyte counts. Three years ago, venetoclax was added to her treatment alongside ibrutinib. This combination therapy produced an extraordinary result—complete remission was achieved, blood counts normalized, lymphadenopathy disappeared, and bone marrow tests showed no trace of residual disease.